Wear Behavior in Dry Sliding of Inconel 600 Alloy Using Taguchi Method and Regression Analysis. (2016) - Banker, Vaishal J.; Mistry, Jitendra M.; Thakor, Malhar R.; Upadhyay, Bhargav H.
Abstract: The main aim of the paper is to study wear behaviour of Inconel 600 alloys by experimental investigation in dry sliding. The Inconel alloys are high-temperature Ni-Based alloy which have various applications like gas turbines, heat exchangers, condensers etc. The Design of experiments technique is used to find out the number of experiments by using Taguchi's L27 orthogonal array which is developed in MINTAB 14 software. The experiments were reduced for the various combinations to get the optimal parameters. The sliding tests are performed on a pin-on-disc tribometer. Regression model made was adequate as the values of R 2 and R 2 (adj) were above 90%. With the help of a work-rate model wear coefficient was found as 2 x 10 -13 Pa -1 or m 2 /N for Inconel 600 and was in good agreement with the previous investigations.